Shaft bracket strength assessment based on seizing and blade loss methods - Firmandha Topan; Yudi Oktovianto Muhammad; Anggara Sony (Zhongguo Jianchuan Yanjiu, 2019)
[Objectives] Classification societies have issued minimum requirements regarding dimensions of shaft bracket,e.g. thickness and cross-section area. However,in practice,the varying requirements of each classification society provide different levels of safety. This is an important issue for designers in determining strength standards for new buildings or existing ships which are intended to undergo a transfer of class. Hence,further study is required to establish the actual minimum requirements.[Methods] In this study,seven ship models registered in Class A are used as samples to compare the requirements of eight classification societies,labelled Classes A to H in the following discussion. Firstly,the seizing and blade loss methods are adopted to devive the formula of shaft bracket in rules,and their feasibility is proved. Then,the I-strut and V-strut shaft bracket are modelled by the two methods to determine the actual minimum size requirements.[Results] The results show that there is a number of assumptions that were used by the classification societies regarding the loading conditions,boundary conditions,shape, cross-section area and bracket length,as well as allowable stress.[Conclusions] This study will provide designers with useful references for setting safety limits for shaft bracket strength.